2020
DOI: 10.34172/hpp.2020.49
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to condom use among Filipinos: A systematic review of literature

Abstract: Background: Between 2010 and 2018, the Philippines had a 203% increase in new human immunodeficiency virus (HIV) infections. The use of condoms is an effective and practical means to prevent HIV transmission. The purpose of this study was to identify facilitators and barriers to condom use among Filipinos guided by the Ecological Model of Health Promotion. Methods: A systematic review of literature using electronic databases was performed using the following keywords: "condom," "Filipinos," and "Philippines." … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…The consideration on pleasure is particularly salient in the Philippine context as the perception that condoms are not comfortable to use and causes displeasure has been found to be a barrier to condom use in a previous review. The same review mentions the need for a "collaborative, culturally-sensitive, and population-speci c approach to develop and implement acceptable, sustainable and successful condom use interventions" [7]. This study adds that more than just condom use, interventions should focus on promoting consistent condom use as the bene ts of preventing STIs and unwanted pregnancies can only come from consistent use of condoms.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The consideration on pleasure is particularly salient in the Philippine context as the perception that condoms are not comfortable to use and causes displeasure has been found to be a barrier to condom use in a previous review. The same review mentions the need for a "collaborative, culturally-sensitive, and population-speci c approach to develop and implement acceptable, sustainable and successful condom use interventions" [7]. This study adds that more than just condom use, interventions should focus on promoting consistent condom use as the bene ts of preventing STIs and unwanted pregnancies can only come from consistent use of condoms.…”
Section: Discussionmentioning
confidence: 91%
“…According to the 2017 Philippine National Demographic and Health Survey (NDHS), only 2% of currently married women and 3% of sexually active unmarried women have male partners who have ever used condoms [6]. A systematic review of condom use in the Philippines found 27 studies involving different populations in selected areas throughout the country [7]. The same review have found that the range of prevalence of consistent condom use ranged from 3% among men who have sex with men in Metro Manila to 74% among female sex workers (FSW) in Iloilo City [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 2017 Philippine National Demographic and Health Survey (NDHS), only 2% of currently married women and 3% of sexually active unmarried women have male partners who have ever used condoms [ 8 ]. A systematic review of condom use in the Philippines found 27 studies involving different populations in selected areas throughout the country [ 9 ]. The same review has found that the prevalence of consistent condom use ranged from 3% among men who have sex with men in Metro Manila to 74% among female sex workers (FSW) in Iloilo City [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Favorable attitudes toward condoms have been shown to lead to healthy sexual behaviors ( De Torres, 2020 ; Kim et al, 2021 ), while unfavorable attitudes decrease the likelihood of condom use ( Ajayi et al, 2019 ; Elshiekh et al, 2020 ) and are associated with other sexual risk behaviors, such as multiple sexual partners ( Shamu et al, 2020 ) and sex under the influence of alcohol or drugs ( Davis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%